PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI ISLAMI DAN NUMERASI DI MASJID AL-JIHAD KOTA PALEMBANG - Rohimin; Selly Elia Mustika; Athira Khoirun Nisyah; Rizky Amilia Pratiwi; Deany Afriany (STKIP Subang, 2026)
This study aims to describe the implementation of community empowerment through Islamic education and numeracy at Al-Jihad Mosque, Palembang City. The study employed a descriptive qualitative approach using observation, interviews, and documentation for data collection. Participants included children of the Qur’anic Education Center, mosque youth, mosque administrators, and local community members. The findings showed that the program contributed positively to increasing community participation in educational and religious activities. Numeracy education integrated with Islamic values helped participants apply mathematical concepts in daily life, while Qur’an learning, tahsin, youth studies, and mosque management education strengthened Islamic literacy and community involvement. Therefore, community empowerment through Islamic education and numeracy supports the strengthening of the mosque’s role as a center for learning and community empowerment.